Muscle activity during running in water and on dry land: Matched physiology - Masumoto, K.; Horsch, S. E.; Agnelli, C.; McClellan, J.; Mercer, J. A. (International Journal of Sports Medicine, 2014)
We investigated muscle activity during deep water running (DWR) and treadmill running on dry land (TMR) at similar physiological responses. 9 subjects (30.7±10.4 years) participated in this study. The baseline conditions consisted of TMR at 3 ratings of perceived exertion (RPE) level (RPE 11, 13, and 15) with heart rate (HR) recorded during each condition. The target HR for each level of DWR condition was determined by the HR recorded during the TMR. Muscle activity from the rectus femoris (RF), biceps femoris (BF), tibialis anterior (TA), and gastrocnemius (GA) were measured. As originally planned, HR was not different between modes (P>0.05) and was different between exercise intensities (P<0.001). Only TA muscle activity was influenced by the interaction of mode and intensity (P<0.05). Muscle activity from the GA during DWR was significantly lower than that of TMR (a 34-48% decrease; P<0.05), although muscle activity from the remaining tested muscles were not influenced by modes of exercise (P>0.05). These observations suggest that matching HR can be recommended to produce similar magnitude of lower extremity muscle activity during DWR to that of TMR, with the exception of the GA.